Species Identification among Fish Samples taken from Mangrove Ecosystem in Lampung Coastal Bay through DNA Barcoding Technique - Yanti Ariyanti; Ika Agus Rini; Novriadi Novriadi; Fidya Septiana (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2023)
Mangrove forests are essential for supporting the habitats of numerous fish species, some of which are vital for local economies. These forests serve as breeding and nurturing environments for fish, providing a safe haven for juvenile fish and protecting them from predators and environmental stressors. There are many different species of fish that use mangrove forests as a breeding and nursery ground. Although many studies on the biodiversity of mangrove organisms on Sumatra Island exist, data on fish species diversity in Lampung Bay is still lacking. Morphological identification is often inadequate to distinguish between potential fish species, even across different life stages such as adults, juveniles, or larvae. However, DNA barcoding has the potential to identify species at any developmental stages accurately. Thus, this study aimed to identify and confirm fish species originating from the mangrove ecosystem in Lampung Bay specifically the Sebalang Mangrove Ecopark (South Lampung) and Petengoran Mangrove Forest, Gebang Village (Pesawaran), through a molecular approach using DNA barcoding techniques. Twenty samples can be identified at the species/genus level, demonstrating that using short, standardized genetic region Cytochrome c oxidase I (COI) mitochondrial gene sequences can accurately and quickly classify fish samples. Furthermore, twenty mitochondrial DNA sequences of various fishes have been submitted to the massive genetic database, GenBank. By identifying species accurately and quickly, DNA barcoding can improve the knowledge about fish biodiversity especially samples taken from the mangrove ecosystem in Lampung Coastal Bay.